COVID‐19 in a case with Kikuchi‐Fujimoto disease. Issue 3 (5th January 2021) - Jaseb, Kaveh; Nameh Goshay Fard, Najmeh; Rezaei, Nima; Sadeghian, Siavash; Sadeghian, Saeid
Key Clinical Message: The accurate diagnosis of Kikuchi‐Fujimoto disease can protect children from unnecessary diagnostic procedures and treatments. Also, the co‐occurrence of rare diseases with other diseases can improve or worsen the symptoms of the patients. Abstract : The accurate diagnosis of Kikuchi‐Fujimoto disease can protect children from unnecessary diagnostic procedures and treatments. Also, the co‐occurrence of rare diseases with other diseases can improve or worsen the symptoms of the patients.